Alternativas de control del nemátodo Meloidogyne spp en el cultivo de papaya (Carica papaya L. - León Llumiguano, Ángel Ricardo (2020)
In Ecuador, papaya (Carica papaya L.), is an important species in the country's economy, due to its high-yielding fruit and the essential nutritional value for the organism, this species is widely appreciated for being one of the few fruit trees that It produces continuously throughout the year after fruiting has begun. The papaya is prone to being attacked by various pests that cause a significant productive loss, among them the nematodes, with Meloidogyne spp being the most damaging for the crop because it produces direct and indirect damage. Phytoparasitic nematodes such as Meloidogyne spp are a group of microscopic worms that live in the soil and are considered a high impact pest in any agrosystem due to their pathogenic action on plants, making it impossible to maintain economically viable agriculture. Annual economic losses are estimated to be around $10 billion in world agricultural production, a problem because most farmers and even technicians possess only basic knowledge about nematodes and their control. Among the control methods, the use of chemical products is the most common, since it causes an enormous population reduction of the nematode and minimizes short-term losses, however, the use of nematicidal chemical compounds has been shown to have a high risk of environmental contamination and can be harmful to producers and consumers. For this reason, it is essential to develop control strategies whose objective is not the complete eradication of the nematode, but its manipulation until achieving a reduction in its population density below the threshold of crop damage, through the integrated use of different control methods. in a certain period of time. This will contribute to maintaining environmental quality and reducing economic losses suffered by producers.